Reflections on group psychotherapy - Tony White (Edukacyjna Analiza Transakcyjna)
Group therapy is one of the foundation forms of psychotherapy that has occurred over the years. It has been used in a multitude of ways and varies widely in how it is structured, how many clients are involved and so forth. Eric Berne’s original practice of transactional analysis was a group therapy because this way he could see the transactions between the various group members. I have used the group approach to psychotherapy for over forty years and this paper looks at just a few of the reflections, observations and techniques that I have developed for group therapy in that time. This includes the three different types of permissions, use of the carom transaction in group therapy, the role of the immediate transactional relationship and the commonality between group therapy and family therapy.